Hà Nội Reminiscences Of Thousand Years - Nguyễn Việt Hà (Nhà xuất bản Kim Đồng, 2024)
"Most iconic symbols of Hanoi, the remarkable 1000-year-old city, are depicted in Hanoi -Reminiscences of thousand years. This book is designed with a special pop-up effect to bringyou along on the most interesting journey, exploring eleven famous historic sights of this capitalcity and the precious heart of Vietnam." -- Publisher's information
Pop-up Book / Sách pop-up
Keywords: Sehenswürdigkeit; Geschichte; Hanoi; Bilderbuch